The effect of drainage, fertilizers, and agro-reclamation techniques on spring wheat productivity - Yu. I. Mitrofanov; L. V. Pugacheva; M. V. Gulyaev; N. K. Pervushina (Зерновое хозяйство России)
The current study was conducted at the agricultural site ‘Gubino’ of the All-Russian Research Institute of Reclaimed Lands (Tver Region) in 2011–2022.   The purpose was to study the efficiency of drainage of waterlogged soils, fertilizers and agro-reclamation techniques when growing spring wheat in the conditions of the North-Western part of the Non-Blackearth region.   The soil of the agricultural site was soddy-podzolic, light loamy and gleyic sandy loam, drained by closed drainage. The field trials have established the influence of drainage of gleyic soils, the use of fertilizers, volumetric slotting of the soil to a depth of 45–50 cm, ridge plowing and ridge belt-scattering method of sowing on spring wheat productivity. Drainage increased wheat productivity on the extensive background by 17.8 % (0.34 t/ha), on the medium-intensive and intensive background by 16.9–19.4 % (0.56–0.60 t/ha). Mineral fertilizers improved productivity more significantly, against a drained background, wheat productivity increase at medium fertilizer rates (N45Р15K45) was 1.20 t/ha (53.3 %) and at high fertilizer rates (N90Р30K90) it was 1.91 t/ha (84.9 %). The combined effect of drainage and fertilizers improved spring wheat productivity on waterlogged soil by 2.2 times (by 2.25 t/ha). The highest payback of 1 kg of fertilizers by a spring wheat yield was obtained on a drained plot with average fertilizer application rates of 9.8 kg of grain. A high effect was obtained from agro-reclamation techniques aimed at improving the water-air regime of soil. With volumetric slotting of the soil, spring wheat productivity raised by 0.50–0.97 t/ha (13.2–26.4 %), with ridge plowing by 0.36 t/ha (12.0 %), with ridge belt-scattering method of sowing with growing spring wheat on ridges 40–80 mm high by 0.45 t/ha or 13.7 %, in relation to the existing technology of row sowing. The study results can be used in the development of adaptive agricultural technologies for cultivating spring wheat on drained lands.